Optimization of convective drying parameters for osmosed button mushroom (Agaricus bisporus) - Mehta, B K; Jain, S K; Sharma, G P; Doshi, A; Jain, H K (Mushroom Research, 2015)
The full factorial completely randomized design (CRD) was adopted for analysis. Two independent process variables (drying temperature and air velocity) having five levels of drying temperature (45, 55, 65, 75 and 85 Â°C) and three levels of air velocity (1.0, 1.5 and 2.0 m/s), a total of fifteen experiments were performed for maximizing ascorbic acid and colour (L-value) and minimizing water activity and drying time as responses for each treatment. Influence of various factors was analysed using ANOVA technique. Second order model was fitted in independent variables and various responses using multiple regression analysis. The optimization of input parameters (drying temperature and air velocity) was carried out using numerical optimization technique with the help of design expert 8.0.6 statistical software. The optimum operating conditions were: drying temperature 65 Â°C and air velocity 2.0 m/s. At this optimum point, drying time, ascorbic acid, colour (L-value) and water activity were predicted to be 450min, 26.71mg/100g dm, 60.99 and 0.321 respectively.